Organ Donation Video Messaging in Motor Vehicle Offices: Results of a Randomized Trial. (December 2015) - Rodrigue, James R.; Fleishman, Aaron; Fitzpatrick, Sean; Boger, Matthew
Context—: Since nearly all registered organ donors in the United States signed up via a driver's license transaction, motor vehicle (MV) offices represent an important venue for organ donation education. Objective—: To evaluate the impact of organ donation video messaging in MV offices. Design—: A 2-group (usual care vs usual care + video messaging) randomized trial with baseline, intervention, and follow-up assessment phases. Setting—: Twenty-eight MV offices in Massachusetts. Intervention—: Usual care comprised education of MV clerks, display of organ donation print materials (ie, posters, brochures, signing mats), and a volunteer ambassador program. The intervention included video messaging with silent (subtitled) segments highlighting individuals affected by donation, playing on a recursive loop on monitors in MV waiting rooms. Main Outcome Measures—: Aggregate monthly donor designation rates at MV offices (primary) and percentage of MV customers who registered as donors after viewing the video (secondary). Results—: Controlling for baseline donor designation rate, analysis of covariance showed a significant group effect for intervention phase ( F = 7.3, P = .01). The usual-care group had a significantly higher aggregate monthly donor designation rate than the intervention group had. In the logistic regression model of customer surveys (n = 912), prior donor designation (β = −1.29, odds ratio [OR] = 0.27 [95% CI = 0.20–0.37], P < .001), white race (β = 0.57 OR = 1.77 [95% CI = 1.23–2.54], P = .002), and viewing the intervention video (β = 0.73, OR = 1.54 [95% CI = 1.24–2.60], P = .01) were statistically significant predictors of donor registration on the day of the survey. Conclusion—: The relatively low uptake of the video intervention by customers most likely contributed to the negative trial finding.